Primera cita en España de Psyllaephagus bliteus Riek (Hymenoptera, Encyrtidae), parasitoide de Glycaspis brimblecombei Moore (hemiptera, Psyllidae) - Perez-Otero, R.=700 1 Borrajo, P.; Mansilla, J.P.; Ruiz, F.
(Es, En)
Ilus; 13 ref.
Keywords: PSYLLAEPHAGUS; HYMENOPTERA; PARASITOIDES; PSILAS; CONTROL BIOLOGICO; EUCALYPTUS; ESPAÑA; GLYCASPIS BRIMBLECOMBEI; BOLETIN DE SANIDAD VEGETAL: PLAGAS